Optimization of Ground Coffee Production Capacity using the Theory of Constraints at PT. XYZ - Ni’am, Minhajun; Sumiati, Sumiati (Sistemasi: Jurnal Sistem Informasi, 2025)
PT XYZ is a company engaged in the ground coffee processing industry, producing both Arabica and Robusta coffee. The company faces a production capacity issue, as output does not meet the target due to imbalances between machine capacities and standard processing times. These bottlenecks result in work-in-progress accumulation at workstation 2 and 4, causing delays and unfulfilled orders. This study adopts the Theory of Constraints (TOC) approach, focusing on addressing constraints in the ground coffee production line. Rough-Cut Capacity Planning (RCCP) analysis identified the main constraints at workstation 2 (roasting) and workstation 4 (finishing). The recommended improvement involves adding two hours of overtime at both workstations from March 2024 to February 2025. This intervention led to a 7.42% increase in Arabica coffee production, from 7,815 kg to 8,395 kg, and a 19.69% increase in Robusta coffee production, from 6,533 kg to 7,819 kg. The improvement also resulted in a rise in company profit from IDR 1,115,060,000 to IDR 1,227,326,000, reflecting a 9.2% increase. These findings demonstrate that the proposed solution effectively optimizes production capacity and enhances company profitability.